Proceedings of the 2020 Computers and People Research Conference 2020
DOI: 10.1145/3378539.3393858
|View full text |Cite
|
Sign up to set email alerts
|

Applying Enterprise Architecture for Digital Transformation of Electro Mobility towards Sustainable Transportation

Abstract: Electro Mobility (eMobility) involves deploying Information and Communication Technologies (ICT) and electric technologies in vehicles to enable electric propulsion of vehicles referred to as Electric Vehicles (EVs). EVs are key infrastructure for achieving a sustainable energy future since EV usage can support in achieving CO2 reduction. However, the deployment of EVs for eMobility is highly dependent on data integration of mobility solutions from different stakeholders involved in urban transportation. Respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Findings reveal that knowledge transfer and availability of support service positively influence perceived usefulness of EA. This result is in line with findings from prior studies (Jnr, 2020;Jnr et al, 2020a, b) where the authors suggested that knowledge as information availability positively determines IS use by practitioners in collaborative enterprise. Likewise, Moscoso-Zea et al (2016); Assar and Hafsi (2019) stated that knowledge management and service support plays a substantial role in the use of EA in relation to business intelligence.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Findings reveal that knowledge transfer and availability of support service positively influence perceived usefulness of EA. This result is in line with findings from prior studies (Jnr, 2020;Jnr et al, 2020a, b) where the authors suggested that knowledge as information availability positively determines IS use by practitioners in collaborative enterprise. Likewise, Moscoso-Zea et al (2016); Assar and Hafsi (2019) stated that knowledge management and service support plays a substantial role in the use of EA in relation to business intelligence.…”
Section: Discussionsupporting
confidence: 92%
“…Table 2 also shows the mean and standard deviations (SD) of the variables, where the mean score for the Likert scale gathered from the respondents suggests that the mean scores are greater than 2.5 as suggested by Bokolo and Petersen (2019) based on the 5-point Likert scale which is greater than 3.00 which is reflected as a significant criteria to determine the respondents acceptance and adoption of EA. Moreover, the SD values are close to 0 and lower than 1; thus, the responses from the respondents are not widely distributed (Jnr, 2020;Jnr et al, 2020a, b). Furthermore, the discriminant validity is assessed whether two factors are statistically different from each other.…”
Section: Analysis Of Measurement Modelmentioning
confidence: 96%
See 1 more Smart Citation
“…Accordingly, municipality authorities are commissioning various measures as initiatives to promote green urban mobility to lessen the negative impact of public transportation on urban residents’ quality of life (Brandajs and Russo, 2023). Therefore, green urban mobility measures are being implemented in many cities aimed at reducing environmental pollution, road congestion and uncontrolled urban development (Anthony, 2020; Balsas, 2023). Green urban mobility measures offer initiatives to increase the efficiency of the public transportation and enhance the attractiveness of the local environment (Jacyna and Kotylak, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, few researches have been conducted in order to increase the flexible and efficient mainstream integration of EVs by citizens. As in reference [4], the author used an enterprise architecture strategy to support the digital transformation of EVs for electro mobility toward sustainable mobility in one of these studies. The author aspired to integrate data from many stakeholders and systems involved in urban mobility services in order to accomplish data integration of electric mobility solutions.…”
Section: Introductionmentioning
confidence: 99%